Tobacco use in older adults in Ghana: sociodemographic characteristics, health risks and subjective wellbeing - Yawson, A.E.; Baddoo, A.; Hagan-Seneadza, N.A; Calys-Tagoe, B.; Hewlett, S.; Dako-Gyeke, P.; Mensah, G.; Minicuci, N.; Naidoo, N.; Chatterji, S.; Kowal, P.; Biritwum, R. (My University, 2013)
Abstract Background Tobacco use over the life-course threatens to increase disease burden in older adulthood, including lower income countries like Ghana. This paper describes demographic, socioeconomic, health risks and life satisfaction indices related to tobacco use among older adults in Ghana. Methods This work was based on the World Health Organization’s multi-country Study on global AGEing and adult health (SAGE), conducted in six countries including Ghana. Wave one of SAGE in Ghana was conducted in 2007-2008 as collaboration between WHO and the University of Ghana Medical School through the Department of Community Health. A nationally representative sample of 4305 older adults aged 50 years and above were interviewed. Associations between tobacco consumption and sociodemographic, socioeconomic, health risk and life satisfaction were evaluated using chi-square and odds ratio (OR). Logistic regression analyses, adjusted for age, sex and other variables, were conducted to determine predictors of tobacco consumption in older persons. Results Overall prevalence of current daily smokers among older adults in Ghana was 7.6%. Tobacco use (i.e. ever used tobacco) was associated with older males, (AOR = 1.10, CI 1.05-1.15), older adults residing in rural locations (AOR = 1.37, CI 1.083-1.724), and older adults who used alcohol (AOR = 1.13, CI 0.230-2.418). Tobacco use was also associated (although not statistically significant per p-values) with increased self-reporting of angina, arthritis, asthma, chronic lung disease, depression, diabetes, hypertension, and stroke. Older adults who used tobacco and with increased health risks, tended to be without health insurance (AOR = 1.41, CI 1.111-1.787). Satisfaction with life and daily living was much lower for those who use tobacco. Regional differences existed in tobacco use; the three northern regions (Upper East, Northern and Upper West) had higher proportions of tobacco use among older adults in the country. Quitting tobacco use was higher in the 70+ years age group, in women, among urban residents and in those with at least secondary education. Quitting tobacco use also increased with increasing income levels. Conclusions Tobacco use among older adults in Ghana was associated with older men living in rural locations, chronic ill-health and reduced life satisfaction. A high proportion of older adults have stopped using tobacco, demonstrating the possibilities for effective public health interventions. Health risk reduction strategies through targeted anti-smoking health campaigns, improvement in access to health and social protection (such as health insurance) will reduce health risks among older persons who use tobacco.